Assessment of phenolic compounds and antioxidant activity in different plants parts of sorghum landraces - Zaitri, Mohamed; Belhadi, Badreddine; Benalia, Mohamed; Ouldkiar, Redha; Souilah, Rachid; Djabali, Djaffar (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
The field of animal feed production it is consider one of the most important areas in livestock production. Given that the livestock sector in Algeria faced many problems, such as water scarcity and the high cost of traditional feed, it is important to find other local sources to overcome those difficulties. This study aimed to determine the content of secondary metabolites, including total phenolic compounds, tannins, and flavonoids, and the antioxidant activities in different parts (leaves, stems, and panicle residues) of ten landraces of sorghum found in the Algerian desert and cultivated in the Bordj Bou Arreridj region of Algeria. The results showed significant differences between the contents of the studied samples, as well as among the three different parts of the plant, namely the leaves, stems, and panicle residues. The total phenolic content ranged from 122.33 to 1344.44 mg EAG.100 g-1, with tannin levels from 4.84 to 927.78 mg EAG.100 g-1, while the flavonoid values ranged from 0.24 to 558.25 mg EQ.100 g-1. The antioxidant activitie also showed a significant variation, with DPPH values between 46.10 and 1481.68 mg AAE.100 g-1, FRAP from 31.76 to 1145.92 mg AAE.100 g-1, and ABTS values ranging from 28.89 to 459.92 mg AAE.100 g-1. These results confirmed that the sorghum plants not only represented a source of primary metabolic compounds such as fibers, starch, proteins, and energy materials used as animal feed, but they could also be utilized as a rich source of phenolic compounds with effective value in the health field.